2017
DOI: 10.3389/fmicb.2016.02144
|View full text |Cite
|
Sign up to set email alerts
|

Lack of the COMPASS Component Ccl1 Reduces H3K4 Trimethylation Levels and Affects Transcription of Secondary Metabolite Genes in Two Plant–Pathogenic Fusarium Species

Abstract: In the two fungal pathogens Fusarium fujikuroi and Fusarium graminearum, secondary metabolites (SMs) are fitness and virulence factors and there is compelling evidence that the coordination of SM gene expression is under epigenetic control. Here, we characterized Ccl1, a subunit of the COMPASS complex responsible for methylating lysine 4 of histone H3 (H3K4me). We show that Ccl1 is not essential for viability but a regulator of genome-wide trimethylation of H3K4 (H3K4me3). Although, recent work in Fusarium and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 98 publications
(147 reference statements)
2
62
0
Order By: Relevance
“…Although disruption of cclA was found to affect growth in several filamentous fungi (Palmer et al , ; Studt et al , ), deletion of cclA as well as overexpression of kdmB did not have an impact on E. festucae development in axenic culture. No changes in morphology or growth rate were observed on PD agar, as well as under salt and pH stress conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although disruption of cclA was found to affect growth in several filamentous fungi (Palmer et al , ; Studt et al , ), deletion of cclA as well as overexpression of kdmB did not have an impact on E. festucae development in axenic culture. No changes in morphology or growth rate were observed on PD agar, as well as under salt and pH stress conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests a repressive influence of H3K4me3 on the respective SM gene clusters in the WT background, because this mark was decreased in both Δ set1 and OE:: KDM5 , and accordingly increased in Δ kdm5 genome‐wide. These results are in accordance with a previous study, where we have observed an increase in BIK and FUS biosynthesis (FSR was not tested) upon deletion of CCL1 , also showing reduced levels of H3K4me3 genome‐wide (Studt et al ., ). However, in Δ ccl1 , H3K4me2/me3 levels were not affected at FUS cluster genes, and H3K4me2 was elevated at BIK cluster genes with unchanged H3K4me3 levels (Studt et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…These results are in accordance with a previous study, where we have observed an increase in BIK and FUS biosynthesis (FSR was not tested) upon deletion of CCL1 , also showing reduced levels of H3K4me3 genome‐wide (Studt et al ., ). However, in Δ ccl1 , H3K4me2/me3 levels were not affected at FUS cluster genes, and H3K4me2 was elevated at BIK cluster genes with unchanged H3K4me3 levels (Studt et al ., ). Contrary to this, the Δ set1 mutant showed a complete loss of all detectable H3K4me2 and H3K4me3.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations